The Importance of Wikis in Foreign Language Learning - Medic, Branko; Sun, Xiaohui (The journal of contemporary issues in business and government, 2021)
In the 21st century, teachers across disciplines are harnessing the power of technology to enhance students‟ learning. Research has been and is continuously being, conducted and theories are continuously being updated to provide new insights into how technological tools such as the internet, blogs, wikis, smart boards, can enhance learning outcomes within classrooms. Teachers have a responsibility to continue to adapt their teaching practices and methodologies to best suit the context they and their students are in. In the digital age, this includes staying informed about the field of technology and ways it can be used to enhance learning. For instance, as a foreign language teacher, who teaches at a college of applied sciences, I have found that technology can play an extremely important role in enhancing students‟ learning. However, I recognize that the way I choose to bring technology into my classroom needs to be informed by research, theory and my critical reflections on current research and theory that centers around technology and learning.